The Urgency of Holistic Education in Muhammadiyah Schools - Hendro Widodo; Sutrisno Sutrisno; Farida Hanum (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
This article focuses on the importance of implementing holistic education in Muhammadiyah schools. The essence of education is to develop the full potentials of humanity covering the potentials of cognitive, emotional, social, spiritual, creativity, and physical. The six potential humanities are a unity, which means a potential can be developed through another potential. Partial views of teachers on the potential of students have implications for non-intact practice of education in schools that make split personality on students. Muhammadiyah education as a part of the national education system is the mandate of the constitution to produce holistic man through education in Muhammadiyah schools. This article is based on research results at Muhammadyah Sleman Yogyakarta Elementary School.